Diclofenac induced-acute kidney injury is linked with oxidative stress and pro-inflammatory changes in Sprague Dawley rats - Alkuraishy, Hayder M.; Al-Gareeb, Ali I.; Hussien, Nawar Raad (Journal of Contemporary Medical Sciences, 2019)
Objectives: Diclofenac induces oxidative stress in the body and became the main cause of nephrotoxicity and acute kidney injury (AKI). The traditional markers of AKI are blood urea and serum creatinine which are regarded as low sensitive and low specific in detection the early renal damage. Therefore, the aim of present study was to evaluate oxidative stress and pro-inflammatory biomarkers in diclofenac induced- AKI in rats. Methods: Twenty Sprague Dawley Male rat were used and randomly divided in to 2 groups. Group1 (n=10): Rats treated with distilled water plus normal saline for 12 days. Group2 (n=10) : Rats treated with distilled water plus diclofenac 15mg/kg for 12 days. Rat body weight, body mass index and estimated glomerular filtration rate (eGFR) were evaluated in both groups. Blood urea, serum creatinine, serum malondialdehyde (MDA), superoxide dismutase (SOD), glutathione reductase (GSH), Neutrophil Gelatinase Associated Lipocalin (NGAL) , kidney injury molecules (KIM-1) and Cystatin-c were estimated. Results: Diclofenac 15mg/kg led to significant AKI through elevation of blood urea and serum creatinine with significant reduction of eGFR. KIM-1 serum level was significantly elevated with high sensitivity and specificity compared to the other tested biomarkers. Conclusion: KIM-1 serum level is more sensitive and specific with high accuracy compared to the other renal biomarkers in diclofenac induced- AKI. Estimation of KIM-1 serum levels should be regarded as a cornerstone for early detection of AKI in high risk patients.